2006
DOI: 10.1677/joe.1.07047
|View full text |Cite
|
Sign up to set email alerts
|

Human neurons express type I GnRH receptor and respond to GnRH I by increasing luteinizing hormone expression

Abstract: Gonadotropin-releasing hormone receptor I (GnRHR I) has been localized to the limbic system of the rat brain, although the functional consequences of GnRH signaling through these receptors is unknown. In this paper, we characterize the expression of GnRHR I in the human hippocampus and cortex, and the functionality of GnRHR I in human neuroblastoma cells. Robust GnRHR I immunoreactivity was detected in the cell body as well as along the apical dendrites of pyramidal neurons in the CA2, CA1, and end plate, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 76 publications
(47 reference statements)
6
50
0
Order By: Relevance
“…These mapping experiments have revealed the wide distribution of GnRH cells and terminals in several extrahypothalamic regions. These observations raise the intriguing possibility that GnRH signals to GnRH receptor-expressing neuronal populations dispersed in several brain regions (Granger et al, 2004;Wilson et al, 2006) to modulate as yet unexplored nonreproductive functions, such as the recently proposed regulation of systemic aging (Zhang et al, 2013). Notably, in addition to the extensive GnRH fiber distribution in those areas, GnRH is also present in the cerebrospinal fluid at concentrations proportional to those detected in the portal blood vessels (Van Vugt et al, 1985) and might thus represent an additional source of GnRH that could potentially signal to multiple brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…These mapping experiments have revealed the wide distribution of GnRH cells and terminals in several extrahypothalamic regions. These observations raise the intriguing possibility that GnRH signals to GnRH receptor-expressing neuronal populations dispersed in several brain regions (Granger et al, 2004;Wilson et al, 2006) to modulate as yet unexplored nonreproductive functions, such as the recently proposed regulation of systemic aging (Zhang et al, 2013). Notably, in addition to the extensive GnRH fiber distribution in those areas, GnRH is also present in the cerebrospinal fluid at concentrations proportional to those detected in the portal blood vessels (Van Vugt et al, 1985) and might thus represent an additional source of GnRH that could potentially signal to multiple brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…In CPP, premature activation of the hypothalamic GnRH neuronal network is the inciting event, stimulating pituitary secretion of FSH and LH, which then trigger ovarian estrogen production. While the GnRH neuropeptide has traditionally been thought to be confined to the hypothalamic median eminence, the identification of the GnRH peptide 31 and the GnRH receptor 32 in human cerebral cortex indicates the potential for extra-hypothalamic functions.…”
Section: Discussionmentioning
confidence: 99%
“…CPP participants and study controls demonstrated a similar distribution of chronotype scores, with the average score in both groups falling within the "intermediate" category, defined as scores of 24-32 (CPP: 27.5 ± 1.7 ; controls: 25.2 ± 3.1 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]). Suppressive therapy with a GnRHa and/or the passage of time had no effect on CPP participants' morningness/ eveningness preference, and chronotype did not correlate with chronologic age or stage of breast development in combined analyses of CPP participants and study controls (r = −0.06, p > .05 for both tests).…”
Section: Chronotype In Cpp Participants and Study Controlsmentioning
confidence: 99%
“…Actually, studies using GnRHa leuprolide therapy, aimed at down regulating peripheral LH, show a decrease the toxic Ab load in the brain and a significant improvements in cognitive performance. 33,37,39 Animal studies utilizing GnRHR antagonists, (cetrorelix), which also lowers serum levels of LH, also show cognitive improvements. 40 More recently, it has been reported a higher hippocampal level of GnRH and GnRHR mRNA in both male and female plaque-bearing AD transgenic mice (tgArcSwe), respect to age matched controls.…”
Section: -32mentioning
confidence: 99%